MO303: Impact of Dexamethasone and Inhaled Nitric Oxide on Severe Acute Kidney Injury in Critically ill Patients With COVID-19. (3rd May 2022) - Bobot, Mickaël; Tonon, David; Peres, Noémie; Guervilly, Christophe; Lefèvre, Flora; Carvelli, Julien; Papazian, Laurent; Max, Howard; Leone, Marc; Lopez, Alexandre; Bommel, Youri; Volff, Maxime; et al.
Abstract: BACKGROUND AND AIMS: Kidney failure is the second most frequent condition after acute respiratory distress syndrome (ARDS) in critically ill patients with severe COVID-19 and is strongly associated with mortality. The aim of this multicentric study was to assess the impact of the specific treatments of COVID-19 and ARDS on the risk of severe acute kidney injury (AKI) in critically ill COVID patients. METHOD: Data from a prospectively collected database of consecutive patients hospitalized in six ICUs for COVID-19 was retrospectively analysed. The incidence and severity of AKI were monitored during the entire ICU stay. Patients older than 18 years hospitalized in for COVID-19-related ARDS requiring mechanical ventilation were included. RESULTS: A total of 164 patients were included in the final analysis, 97 (59.1%) displayed AKI, of which 39 had severe stage 3 AKI and 21 (12.8%) requiring renal replacement therapy (RRT). In univariate analysis, severe AKI was associated with ACEI exposure ( P = .016), high blood pressure ( P = .029), APACHE-II score ( P = .004) and mortality at D28 ( P = .008), D60 ( P < .001) and D90 ( P < .001). In multivariate analysis, the factors associated with the onset of stage 3 AKI were: exposure to CEI [OR: 4.238 (1.307–13.736); P = .016], APACHE II score (without age) [OR: 1.138 (1.044–1.241); P = .003] and iNO [OR: 5.694 (1.953–16.606); P = .001], protective factors were prone positioning [OR: 0.234 (0.057–0.967); P = .045] and dexamethasone [OR: 0.194 (0.053–0.713); P = .014]. CONCLUSION: Dexamethasone seems to prevent the risk of severe AKI and RRT, and iNO seems associated with severe AKI and RRT in critically ill patients with COVID-19. iNO must be used with caution in COVID-19 related ARDS.